Book Review - Engaging in Action Research: A Practical Guide to Teacher-Conducted Research for Educators & School Leaders - Mark Dziedzic (Networks: An Online Journal for Teacher Research, 2016)
As might be expected, Networks regularly features reviews of books related to action research in educational settings. In a previous review (Networks, 15/1), Hartlep described Voices from the Classroom (Sargent, 2009) as a useful text for supporting educators interested in conducting action research, particularly teacher researchers who focus on improving classroom instruction. Hartlep suggested that the book might not have sufficient scholarly emphasis for those pursuing action research in order to contribute to scholarly literature. In this review, I argue that Parson, Hewson, Adrian, and Day’s Engaging in Action Research: A Practical Guide to Teacher-Conducted Research for Educators and School Leaders (2013) will appeal to a broader audience.